The Diary of a young girl - Frank, Anne; I. Frank, Otto H.; II. Pressler, Mirjam; III. Massotty, Susan (New Delhi : Fingerprint! Pub., 2025)
An Inspiration The Holocaust was one of the most horrendous and terrible eras in history. Innumerable books have been written describing the horrors of the Holocaust; but nothing beats the documentation of a family who had gone into hiding in the diary of a little girl, Anne Frank. Honest, lucid and empathetic; The Diary of A Young Girl deserves a read by everyone who has ever questioned mental strength of humans and also by those who cannot come to terms with the cruelties that could be inflicted by humans upon fellow humans. The first entry in the diary is on June 12, 1942 by Anne Frank, who had received it as a birthday present and the entries in the diary end abruptly on 1 August, 1944. The Underlying Themes Anne Frank and her family lived a peaceful life in Frankfurt, Germany but they had to escape to Amsterdam with fellow Jews and go into hiding, as the Nazis took over Europe. Anne writes in her diary the tribulations her family had to face living in hiding, because they knew if caught, they would have to suffer horribly. The sufferance of the Jews during the Holocaust is known to all; yet a thirteen year old feeling the impact of intolerance and racism makes readers realise how profound the impacts of the World War II was. What is most captivating is that amidst the terror and the fear, Anne manages to remain a cheerful girl full of life, who loved to talk and observe. Still a teenager and unaware of the horrors lurking behind their hiding space, Anne fails to realise the fear trapped within the hearts of elders initially and describes everyday events from the view of a teenager. As the story develops, Anne develops and realisation comes over her. The Nazis are getting more stringent and oppression rises; there are certain places in the book that leaves readers sad and distressed. One day, Anne's entire family including her, gets captured and the diary ends abruptly with the promise of a new day that never comes in the life of Anne Frank. Anne's father, Otto Frank, was the only one in the family who had managed to escape the concentration camps they were taken to and went on to make Anne's diary into a book. Conclusion The story of Anne Frank and the Frankfurt family is considered one of the most insightful accounts of the World War through the eyes of a young girl. The Diary of A Young Girl has been the subject of innumerable plays and movies. The original diary was published by Otto Frank in Dutch in 1947 and it was first translated to English in 1952, as The Diary of A Young Girl. Since then, it has been translated to more than sixty languages and people all over the world have read, loved and cried over the memoirs of Anne Frank. The book is available online for convenient shopping. You can bag this book from A today by following a few easy steps. A Children?s Bookshelf Selection: Each month our editor?s pick the best books for children and young adults by age to be a part of the children?s bookshelf. These are editorial recommendations made by our team of experts. Our monthly reading list includes a mix of bestsellers and top new releases and evergreen books that will help enhance a child?s reading life.
Keywords: 1. History; 2. Holocaust, Jewish -- Personal narratives; 3. Jewish children in the Holocaust -- Diaries; 4. Jews -- Diaries -- Persecutions -- Netherlands -- Amsterdam; 5. World War -- Personal narratives, Jewish